The spiritual well-being of patients with ankylosing spondylitis and rheumatoid arthritis - Raikan Buyukavci; Emine Burcu Comruk; Semra Akturk; Yuksel Ersoy (Medicine Science, 2022)
The aim of this study was to determine the spiritual well-being of patients with ankylosing spondylitis (AS) and rheumatoid arthritis (RA), as well as its relationship with disease activity. The study included a total of 91 patients (43 patients with AS and 48 patients with RA). The patients' demographic data, disease duration, and comorbidities were questioned. Disease activity was evaluated by Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) for AS and by Diseases Activity Score-28 (DAS-28) for RA. The levels of spiritual well-being were evaluated with the Functional Assessment of Chronic Illness Therapy-Spiritual Well-Being (FACIT-Sp-12). The spiritual well-being scores of both patient groups were moderately high. However, RA patients had significantly lower FACIT-Sp-12 meaning and peace sub scores and total scores than AS patients (p=0.04; 0.01; 0.04, respectively). AS patients, on the other hand, had lower faith sub scores than RA patients (p=0.01). The mean DAS-28 was 2.83±0.16 for RA, and the mean BASDAI score was 2.73±0.23 for AS. There was no correlation between FACIT-Sp-12 scores and disease activity levels in both patient groups (p>0.05). We found moderate levels of spiritual well-being in the most common rheumatic diseases such as AS and RA. Although this study demonstrated no relationship between spiritual well-being and disease activity, we believe that as with the quality of life, the spiritual well-being level of patients is a psychosocial variable that should be prioritized in the treatment of chronic rheumatic diseases. [Med-Science 2022; 11(1.000): 299-303]